Clinical and ultrasonic risk factors for high‐volume central lymph node metastasis in cN0 papillary thyroid microcarcinoma: A retrospective study and meta‐analysis - Wang, Zhiyuan; Gui, Zhiqiang; Wang, Zhihong; Huang, Jiapeng; He, Liang; Dong, Wenwu; Zhang, Dalin; Zhang, Ting; Shao, Liang; Shi, Jinyuan; Wu, Pu; Ji, Xiaoyu; et al. (Clinical endocrinology (Oxford), 2023)
Objective Papillary thyroid microcarcinoma (PTMC) comprises more than 50% of all newly detected cases of papillary thyroid carcinoma (PTC). High‐volume lymph node metastasis (involving >5 lymph nodes) (hv‐LNM) is associated with PTMC recurrence. In half of the clinically node‐negative (cN0) PTMC patients, central lymph node metastasis (CLNM) is pathologically present. However, clinical risk factors for high‐volume CLNM (hv‐CLNM) in cN0 PTMC have not been defined well. Therefore, we aimed to obtain evidence for hv‐CLNM risk factors in cN0 PTMC. Design Data on patients who visited our hospital between January 2020 and December 2021 were collected; a preoperative diagnosis of cN0 and a postoperative pathological confirmation of PTMC were obtained. After filtering by inclusion versus exclusion criteria, the obtained data (N = 2268) were included in the meta‐analysis. Relevant studies published as of 10 April 2022, were identified from the Web of Science, PubMed, WANFANG, and CNKI databases. These eligible studies were included in the meta‐analysis and the association between clinicopathological factors and hv‐CLNM in cN0 PTMC was assessed. SPSS and MetaXL were used for statistical analyses. Results The meta‐analysis included 10 previous studies (11,734 patients) and 2268 patients enroled in our hospital for a total of 14,002 subjects. The results of which suggested that younger age (<40, odds ratio [OR] = 3.28, 95% confidence interval [CI] = 2.75–3.92, p < .001 or <45 odds ratio [OR] = 2.93, 95% CI = 2.31–3.72, p < .001), male sex (OR = 2.81, 95% CI = 2.25–3.52, p < .001), tumour size >5 mm (OR = 1.85, 95% CI = 1.39–2.47, p < .001), multifocality (OR = 1.88, 95% CI = 1.56–2.26, p < .001), extrathyroidal extension (OR = 2.58, 95% CI = 2.02–3.30, p < .001), capsule invasion (OR = 2.02, 95% CI = 1.46–2.78, p < .001), microcalcification (OR = 3.25, 95% CI = 2.42–4.36, p < .001) and rich blood flow (OR = 1.65, 95% CI = 1.21–2.25, p = .002) were the significant factors related to an elevated hv‐CLNM risk in cN0 PTMC patients. Hashimoto thyroiditis (OR = 0.76, 95% CI = 0.55–1.07, p = .114), irregular margin (versus regular margin, OR = 0.96, 95% CI = 0.68–1.33, p = .787) and hypoechoic (versus nonhypoechoic, OR = 1.27, 95% CI = 0.84–1.92, p = .261) showed no significant association with hv‐CLNM. Conclusions Younger age, tumour size >5 mm, males, extrathyroidal extension, multifocality, microcalcification, capsular invasion, and rich blood flow were the significant clinicopathological risk factors for hv‐CLNM risk in cN0 PTMC patients. These predictors may compensate for the sensitivity of imaging diagnosis in the preoperative period, thus helping in the effective identification of PTMCs with an invasive phenotype.